Agile methodology: a proposal to improve skills in Vocational Training (Journal of Parents and Teachers, 2015)
The experience carried out is about the integration into the curriculum of the training module forEnterpriseand Entrepreneurship Initiative (EEI) of new methodological procedures, globally called "Agile methodology" and which have become so popular in business environment. Adapting applied methodologies in a successfully way in other areas may be a route of research and practice that provides optimal results in finding employment and could help developing some of the skills considered as essential to the employability of young people, initiative, confidence and communication.
Keywords: Job search; agile methodologies; career guidance; entrepreneurship; vocational training; education; educational guidance